Features of training 3d computer modeling and visualization of future teachers of informatics - O. G. Rylova (Системный анализ и прикладная информатика)
The cognitive, developing, illustrative potential of three-dimensional computer graphics actualizes the training of future teachers in its technologies. The future teacher of computer science should be able to develop three-dimensional models and animations of the studied objects (phenomena and processes) in computer science, physics, mathematics and other academic disciplines, create copyright electronic educational resources with three-dimensional illustrations, apply augmented reality and 3D printing in professional activities.The article describes the features of teaching three-dimensional computer modeling and visualization of future informatics teachers, identified on the basis of an analysis of the training system for students studying in specialty 1–02 05 02 Physics and Informatics at the Maxim Tank Belarusian State Pedagogical University.The main directions for improving the learning process of three-dimensional computer graphics of future informatics teachers are indicated. Questions on three-dimensional computer modeling and visualization will pass through the content line through the content of six academic disciplines («Computer graphics and multimedia», «Computational methods and computer modeling», «Programming Technologies and Algorithmization Methods», «Information Technologies in Education», «Methods teaching informatics» and «Architecture and software of computer systems»). This will ensure consistency in the introduction and study of concepts, the choice of forms and methods of teaching, the development of teaching and methodical support. For the implementation of interdisciplinarity, it is proposed to carry out practice-oriented interdisciplinary educational projects in the framework of the study of academic disciplines in three subject areas «Computer Science», «Physics» and «Mathematics». The development of a methodical system of interdisciplinary education will ensure the formation of readiness to teach three-dimensional graphics at the stage of general secondary education and to realize its didactic possibilities in organizing educational and research activities of students.